Termination w.r.t. Q of the following Term Rewriting System could be proven:
Q restricted rewrite system:
The TRS R consists of the following rules:
p(a(x0), p(x1, p(x2, x3))) → p(x1, p(x0, p(a(x3), x3)))
Q is empty.
↳ QTRS
↳ DependencyPairsProof
Q restricted rewrite system:
The TRS R consists of the following rules:
p(a(x0), p(x1, p(x2, x3))) → p(x1, p(x0, p(a(x3), x3)))
Q is empty.
Using Dependency Pairs [1,15] we result in the following initial DP problem:
Q DP problem:
The TRS P consists of the following rules:
P(a(x0), p(x1, p(x2, x3))) → P(x1, p(x0, p(a(x3), x3)))
P(a(x0), p(x1, p(x2, x3))) → P(x0, p(a(x3), x3))
P(a(x0), p(x1, p(x2, x3))) → P(a(x3), x3)
The TRS R consists of the following rules:
p(a(x0), p(x1, p(x2, x3))) → p(x1, p(x0, p(a(x3), x3)))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ QDPOrderProof
↳ QDPOrderProof
Q DP problem:
The TRS P consists of the following rules:
P(a(x0), p(x1, p(x2, x3))) → P(x1, p(x0, p(a(x3), x3)))
P(a(x0), p(x1, p(x2, x3))) → P(x0, p(a(x3), x3))
P(a(x0), p(x1, p(x2, x3))) → P(a(x3), x3)
The TRS R consists of the following rules:
p(a(x0), p(x1, p(x2, x3))) → p(x1, p(x0, p(a(x3), x3)))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
We use the reduction pair processor [15].
The following pairs can be oriented strictly and are deleted.
P(a(x0), p(x1, p(x2, x3))) → P(x0, p(a(x3), x3))
P(a(x0), p(x1, p(x2, x3))) → P(a(x3), x3)
The remaining pairs can at least be oriented weakly.
P(a(x0), p(x1, p(x2, x3))) → P(x1, p(x0, p(a(x3), x3)))
Used ordering: Polynomial interpretation [25]:
POL(P(x1, x2)) = x2
POL(a(x1)) = 0
POL(p(x1, x2)) = 1 + x2
The following usable rules [17] were oriented:
p(a(x0), p(x1, p(x2, x3))) → p(x1, p(x0, p(a(x3), x3)))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ ForwardInstantiation
↳ QDPOrderProof
Q DP problem:
The TRS P consists of the following rules:
P(a(x0), p(x1, p(x2, x3))) → P(x1, p(x0, p(a(x3), x3)))
The TRS R consists of the following rules:
p(a(x0), p(x1, p(x2, x3))) → p(x1, p(x0, p(a(x3), x3)))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
By forward instantiating [14] the rule P(a(x0), p(x1, p(x2, x3))) → P(x1, p(x0, p(a(x3), x3))) we obtained the following new rules:
P(a(x0), p(a(y_0), p(x2, x3))) → P(a(y_0), p(x0, p(a(x3), x3)))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ ForwardInstantiation
↳ QDP
↳ SemLabProof
↳ QDPOrderProof
Q DP problem:
The TRS P consists of the following rules:
P(a(x0), p(a(y_0), p(x2, x3))) → P(a(y_0), p(x0, p(a(x3), x3)))
The TRS R consists of the following rules:
p(a(x0), p(x1, p(x2, x3))) → p(x1, p(x0, p(a(x3), x3)))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
We found the following model for the rules of the TRS R.
Interpretation over the domain with elements from 0 to 1.P: 0
a: 1
p: 0
By semantic labelling [33] we obtain the following labelled TRS:Q DP problem:
The TRS P consists of the following rules:
P.1-0(a.0(x0), p.1-0(a.0(y_0), p.0-1(x2, x3))) → P.1-0(a.0(y_0), p.0-0(x0, p.1-1(a.1(x3), x3)))
P.1-0(a.0(x0), p.1-0(a.1(y_0), p.1-1(x2, x3))) → P.1-0(a.1(y_0), p.0-0(x0, p.1-1(a.1(x3), x3)))
P.1-0(a.1(x0), p.1-0(a.1(y_0), p.0-0(x2, x3))) → P.1-0(a.1(y_0), p.1-0(x0, p.1-0(a.0(x3), x3)))
P.1-0(a.0(x0), p.1-0(a.0(y_0), p.1-1(x2, x3))) → P.1-0(a.0(y_0), p.0-0(x0, p.1-1(a.1(x3), x3)))
P.1-0(a.1(x0), p.1-0(a.1(y_0), p.1-0(x2, x3))) → P.1-0(a.1(y_0), p.1-0(x0, p.1-0(a.0(x3), x3)))
P.1-0(a.1(x0), p.1-0(a.1(y_0), p.0-1(x2, x3))) → P.1-0(a.1(y_0), p.1-0(x0, p.1-1(a.1(x3), x3)))
P.1-0(a.1(x0), p.1-0(a.0(y_0), p.1-0(x2, x3))) → P.1-0(a.0(y_0), p.1-0(x0, p.1-0(a.0(x3), x3)))
P.1-0(a.1(x0), p.1-0(a.0(y_0), p.0-1(x2, x3))) → P.1-0(a.0(y_0), p.1-0(x0, p.1-1(a.1(x3), x3)))
P.1-0(a.0(x0), p.1-0(a.1(y_0), p.0-0(x2, x3))) → P.1-0(a.1(y_0), p.0-0(x0, p.1-0(a.0(x3), x3)))
P.1-0(a.1(x0), p.1-0(a.0(y_0), p.1-1(x2, x3))) → P.1-0(a.0(y_0), p.1-0(x0, p.1-1(a.1(x3), x3)))
P.1-0(a.0(x0), p.1-0(a.0(y_0), p.0-0(x2, x3))) → P.1-0(a.0(y_0), p.0-0(x0, p.1-0(a.0(x3), x3)))
P.1-0(a.0(x0), p.1-0(a.0(y_0), p.1-0(x2, x3))) → P.1-0(a.0(y_0), p.0-0(x0, p.1-0(a.0(x3), x3)))
P.1-0(a.1(x0), p.1-0(a.0(y_0), p.0-0(x2, x3))) → P.1-0(a.0(y_0), p.1-0(x0, p.1-0(a.0(x3), x3)))
P.1-0(a.1(x0), p.1-0(a.1(y_0), p.1-1(x2, x3))) → P.1-0(a.1(y_0), p.1-0(x0, p.1-1(a.1(x3), x3)))
P.1-0(a.0(x0), p.1-0(a.1(y_0), p.0-1(x2, x3))) → P.1-0(a.1(y_0), p.0-0(x0, p.1-1(a.1(x3), x3)))
P.1-0(a.0(x0), p.1-0(a.1(y_0), p.1-0(x2, x3))) → P.1-0(a.1(y_0), p.0-0(x0, p.1-0(a.0(x3), x3)))
The TRS R consists of the following rules:
p.1-0(a.1(x0), p.0-0(x1, p.0-0(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.1-0(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.0-0(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.0-1(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.1-0(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.0-0(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.1(x0), p.0-0(x1, p.0-1(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.0-0(x1, p.1-0(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.0-1(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.1-1(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.0-0(x1, p.1-1(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.0-1(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.1-1(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.1-1(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.0-0(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.1-0(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ ForwardInstantiation
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ QDPOrderProof
Q DP problem:
The TRS P consists of the following rules:
P.1-0(a.0(x0), p.1-0(a.0(y_0), p.0-1(x2, x3))) → P.1-0(a.0(y_0), p.0-0(x0, p.1-1(a.1(x3), x3)))
P.1-0(a.0(x0), p.1-0(a.1(y_0), p.1-1(x2, x3))) → P.1-0(a.1(y_0), p.0-0(x0, p.1-1(a.1(x3), x3)))
P.1-0(a.1(x0), p.1-0(a.1(y_0), p.0-0(x2, x3))) → P.1-0(a.1(y_0), p.1-0(x0, p.1-0(a.0(x3), x3)))
P.1-0(a.0(x0), p.1-0(a.0(y_0), p.1-1(x2, x3))) → P.1-0(a.0(y_0), p.0-0(x0, p.1-1(a.1(x3), x3)))
P.1-0(a.1(x0), p.1-0(a.1(y_0), p.1-0(x2, x3))) → P.1-0(a.1(y_0), p.1-0(x0, p.1-0(a.0(x3), x3)))
P.1-0(a.1(x0), p.1-0(a.1(y_0), p.0-1(x2, x3))) → P.1-0(a.1(y_0), p.1-0(x0, p.1-1(a.1(x3), x3)))
P.1-0(a.1(x0), p.1-0(a.0(y_0), p.1-0(x2, x3))) → P.1-0(a.0(y_0), p.1-0(x0, p.1-0(a.0(x3), x3)))
P.1-0(a.1(x0), p.1-0(a.0(y_0), p.0-1(x2, x3))) → P.1-0(a.0(y_0), p.1-0(x0, p.1-1(a.1(x3), x3)))
P.1-0(a.0(x0), p.1-0(a.1(y_0), p.0-0(x2, x3))) → P.1-0(a.1(y_0), p.0-0(x0, p.1-0(a.0(x3), x3)))
P.1-0(a.1(x0), p.1-0(a.0(y_0), p.1-1(x2, x3))) → P.1-0(a.0(y_0), p.1-0(x0, p.1-1(a.1(x3), x3)))
P.1-0(a.0(x0), p.1-0(a.0(y_0), p.0-0(x2, x3))) → P.1-0(a.0(y_0), p.0-0(x0, p.1-0(a.0(x3), x3)))
P.1-0(a.0(x0), p.1-0(a.0(y_0), p.1-0(x2, x3))) → P.1-0(a.0(y_0), p.0-0(x0, p.1-0(a.0(x3), x3)))
P.1-0(a.1(x0), p.1-0(a.0(y_0), p.0-0(x2, x3))) → P.1-0(a.0(y_0), p.1-0(x0, p.1-0(a.0(x3), x3)))
P.1-0(a.1(x0), p.1-0(a.1(y_0), p.1-1(x2, x3))) → P.1-0(a.1(y_0), p.1-0(x0, p.1-1(a.1(x3), x3)))
P.1-0(a.0(x0), p.1-0(a.1(y_0), p.0-1(x2, x3))) → P.1-0(a.1(y_0), p.0-0(x0, p.1-1(a.1(x3), x3)))
P.1-0(a.0(x0), p.1-0(a.1(y_0), p.1-0(x2, x3))) → P.1-0(a.1(y_0), p.0-0(x0, p.1-0(a.0(x3), x3)))
The TRS R consists of the following rules:
p.1-0(a.1(x0), p.0-0(x1, p.0-0(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.1-0(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.0-0(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.0-1(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.1-0(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.0-0(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.1(x0), p.0-0(x1, p.0-1(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.0-0(x1, p.1-0(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.0-1(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.1-1(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.0-0(x1, p.1-1(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.0-1(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.1-1(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.1-1(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.0-0(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.1-0(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
The approximation of the Dependency Graph [15,17,22] contains 2 SCCs with 13 less nodes.
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ ForwardInstantiation
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ QDPOrderProof
Q DP problem:
The TRS P consists of the following rules:
P.1-0(a.1(x0), p.1-0(a.1(y_0), p.1-1(x2, x3))) → P.1-0(a.1(y_0), p.1-0(x0, p.1-1(a.1(x3), x3)))
The TRS R consists of the following rules:
p.1-0(a.1(x0), p.0-0(x1, p.0-0(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.1-0(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.0-0(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.0-1(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.1-0(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.0-0(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.1(x0), p.0-0(x1, p.0-1(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.0-0(x1, p.1-0(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.0-1(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.1-1(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.0-0(x1, p.1-1(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.0-1(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.1-1(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.1-1(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.0-0(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.1-0(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
We use the reduction pair processor [15].
The following pairs can be oriented strictly and are deleted.
P.1-0(a.1(x0), p.1-0(a.1(y_0), p.1-1(x2, x3))) → P.1-0(a.1(y_0), p.1-0(x0, p.1-1(a.1(x3), x3)))
The remaining pairs can at least be oriented weakly.
none
Used ordering: Polynomial interpretation [25]:
POL(P.1-0(x1, x2)) = x1 + x2
POL(a.1(x1)) = 1 + x1
POL(p.1-0(x1, x2)) = x1
POL(p.1-1(x1, x2)) = 0
The following usable rules [17] were oriented:
none
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ ForwardInstantiation
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ PisEmptyProof
↳ QDP
↳ QDPOrderProof
Q DP problem:
P is empty.
The TRS R consists of the following rules:
p.1-0(a.1(x0), p.0-0(x1, p.0-0(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.1-0(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.0-0(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.0-1(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.1-0(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.0-0(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.1(x0), p.0-0(x1, p.0-1(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.0-0(x1, p.1-0(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.0-1(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.1-1(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.0-0(x1, p.1-1(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.0-1(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.1-1(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.1-1(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.0-0(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.1-0(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
The TRS P is empty. Hence, there is no (P,Q,R) chain.
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ ForwardInstantiation
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ QDP
↳ QDPOrderProof
↳ QDPOrderProof
Q DP problem:
The TRS P consists of the following rules:
P.1-0(a.1(x0), p.1-0(a.1(y_0), p.0-0(x2, x3))) → P.1-0(a.1(y_0), p.1-0(x0, p.1-0(a.0(x3), x3)))
P.1-0(a.1(x0), p.1-0(a.1(y_0), p.1-0(x2, x3))) → P.1-0(a.1(y_0), p.1-0(x0, p.1-0(a.0(x3), x3)))
The TRS R consists of the following rules:
p.1-0(a.1(x0), p.0-0(x1, p.0-0(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.1-0(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.0-0(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.0-1(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.1-0(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.0-0(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.1(x0), p.0-0(x1, p.0-1(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.0-0(x1, p.1-0(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.0-1(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.1-1(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.0-0(x1, p.1-1(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.0-1(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.1-1(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.1-1(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.0-0(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.1-0(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
We use the reduction pair processor [15].
The following pairs can be oriented strictly and are deleted.
P.1-0(a.1(x0), p.1-0(a.1(y_0), p.0-0(x2, x3))) → P.1-0(a.1(y_0), p.1-0(x0, p.1-0(a.0(x3), x3)))
P.1-0(a.1(x0), p.1-0(a.1(y_0), p.1-0(x2, x3))) → P.1-0(a.1(y_0), p.1-0(x0, p.1-0(a.0(x3), x3)))
The remaining pairs can at least be oriented weakly.
none
Used ordering: Polynomial interpretation [25]:
POL(P.1-0(x1, x2)) = x1 + x2
POL(a.0(x1)) = 0
POL(a.1(x1)) = 1 + x1
POL(p.0-0(x1, x2)) = x2
POL(p.0-1(x1, x2)) = 1 + x2
POL(p.1-0(x1, x2)) = x1 + x2
POL(p.1-1(x1, x2)) = 0
The following usable rules [17] were oriented:
p.1-0(a.0(x0), p.1-0(x1, p.0-0(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.1(x0), p.0-0(x1, p.0-1(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.0-1(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.1-0(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.1-0(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.0-0(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.1(x0), p.0-0(x1, p.0-0(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.1-1(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.0-1(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.1-1(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.1-1(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.0-0(x1, p.1-1(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.0-0(x1, p.1-0(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.0-1(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.1-0(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.0-0(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ ForwardInstantiation
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ PisEmptyProof
↳ QDPOrderProof
Q DP problem:
P is empty.
The TRS R consists of the following rules:
p.1-0(a.1(x0), p.0-0(x1, p.0-0(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.1-0(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.0-0(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.0-1(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.1-0(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.0-0(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.1(x0), p.0-0(x1, p.0-1(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.0-0(x1, p.1-0(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.0-1(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.1-0(x1, p.1-1(x2, x3))) → p.1-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.0-0(x1, p.1-1(x2, x3))) → p.0-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.0-1(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.0(x0), p.0-0(x1, p.1-1(x2, x3))) → p.0-0(x1, p.0-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.1-1(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-1(a.1(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.0-0(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
p.1-0(a.1(x0), p.1-0(x1, p.1-0(x2, x3))) → p.1-0(x1, p.1-0(x0, p.1-0(a.0(x3), x3)))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
The TRS P is empty. Hence, there is no (P,Q,R) chain.
We use the reduction pair processor [15].
The following pairs can be oriented strictly and are deleted.
P(a(x0), p(x1, p(x2, x3))) → P(a(x3), x3)
The remaining pairs can at least be oriented weakly.
P(a(x0), p(x1, p(x2, x3))) → P(x1, p(x0, p(a(x3), x3)))
P(a(x0), p(x1, p(x2, x3))) → P(x0, p(a(x3), x3))
Used ordering: Matrix interpretation [3]:
Non-tuple symbols:
M( p(x1, x2) ) = | | + | | · | x1 | + | | · | x2 |
Tuple symbols:
M( P(x1, x2) ) = | 0 | + | | · | x1 | + | | · | x2 |
Matrix type:
We used a basic matrix type which is not further parametrizeable.
As matrix orders are CE-compatible, we used usable rules w.r.t. argument filtering in the order.
The following usable rules [17] were oriented:
p(a(x0), p(x1, p(x2, x3))) → p(x1, p(x0, p(a(x3), x3)))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ QDPOrderProof
↳ QDPOrderProof
↳ QDP
Q DP problem:
The TRS P consists of the following rules:
P(a(x0), p(x1, p(x2, x3))) → P(x1, p(x0, p(a(x3), x3)))
P(a(x0), p(x1, p(x2, x3))) → P(x0, p(a(x3), x3))
The TRS R consists of the following rules:
p(a(x0), p(x1, p(x2, x3))) → p(x1, p(x0, p(a(x3), x3)))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.